ADTU-03 Impact of improved access to biologic therapies and physician engagement on excess steroid exposure. (8th June 2018) - Parkes, Gareth; Selinger, Christian; Bassi, Ash; Smith, Melissa; Lindi, Jimmi; Ludlow, Helen; Patel, Pritash; Salunke, Santosh; Hall, Veronica; George, Becky; Saunders, John; Adamson, Mark; et al.
Abstract : Background: Steroid free remission is an important goal of IBD therapy. The aim of this study was to evaluate temporal changes in steroid prescribing in UK IBD outpatients in the context of major changes in UK prescribing guidelines and physician participation in audit and tailored service changes. Methods: Steroid use over the previous 12 months was recorded for unselected outpatient attenders against a definition of excess from ECCO guidelines. Data were collected from 7 centres that had completed a steroid assessment audit cycle in 2015, as well as from 12 new matched centres. Results: Data was collected for 2385 patients May-July 2017 and compared with 2015 data from 1176 patients. Overall disease distribution was 47.1% CD, 49.6% UC and 3.3% IBD-U, whilst 77.7% of patients were in clinical remission at the time of assessment. There was only a modest increase in patient exposure to anti-TNF from 2015 to 2017: 30.6% to 37.2% in CD (p=0.009) and 9.9% to 12.0% in UC (p=NS). Anti-integrin usage increased from 0.8% to 3.3% in CD (p=0.002) and from 1.6% to 2.4% in UC (p=NS). For centres taking part in the 2015 audit, steroid exposure rates fell from 30% to 23.8% (p = 0.003) and steroid excess from 13.7% to 11.5% (p = NS). Steroid exposure and excess rates for sites that had not been part of the previous audit were significantly higher (31.0% excess, 17.1% exposure, p=0.0001 for both). There were no significant differences in important baseline characteristics of 2 groups of sites. Logistic regression analysis revealed independent predictors of reduced risk of steroid excess, after correction for disease severity. For CD these included treatment with anti-TNF therapy (p=0.04), treatment in a centre with regular IBD multidisciplinary team (MDT) meetings (p=0.01) and treatment in an original 2015 centre (p=0.02). For UC treatment in a 2015 centre was also significant predictor of protection (p=0.04) and treatment with thiopurine monotherapy a predictor of risk of excess (p=0.01); usage of anti-TNF therapy in UC did not reach significance for protection from excess. Conclusions: Changes in biologic access in the UK have resulted in only modest changes in prescribing behaviour and have not yet impacted significantly on excess steroid exposure in UC, unlike in CD. Participation in an audit cycle of steroid usage was associated with a meaningful reduction in steroid excess. These data support the concept that steroid excess could be used as a key performance indicator in IBD and physicians should be engaged in this process.